Analysis of Soil Penetration Resistance in Coffee Plantation Agroecosystems in Bangelan, Malang, East Java - Riyanto, Saniya Reizta; Hanuf, Atiqah Aulia; Alista, Febri Ayu; Yumna, Alifa; Soemarno, Soemarno (PLANTA TROPIKA, 2022)
Agriculture land shows soil compaction problems due to long-term agricultural cultivation activities. Soil compaction indicator can be seen from the value of soil penetration resistance at different soil depths (0 - 60 cm). This research aimed to determine soil penetration resistance at different coffee plantation ages with different soil depths and to analyze the relationship between soil penetration resistance with soil physical characteristics and coffee productivity. The survey activities include observation of minipits, measuring soil penetration resistance at soil depths of 0-20 cm, 20-40 cm, and 40-60 cm using a hand penetrometer, and soil sampling. The results showed that the soil penetration resistance at each LU and soil depth suggested variation were categorized into moderate and high soil penetration resistance classes (1.34 MPa - 3.35 MPa). Soil characteristics, such as soil aggregate stability, water content, bulk density, porosity, silt content, and clay content, significantly correlate with soil penetration resistance. However, soil penetration resistance has a negative correlation with coffee productivity. The value of soil penetration resistance (at a depth of 0-60 cm) has a significant negative correlation with the average productivity of coffee plantations (r=-0.5936**). Therefore, increased soil penetration resistance decreased root growth, decreasing plant productivity.